Os homófonos não homógrafos em dicionários pedagógicos de língua inglesa: possíveis sugestões lexicográficas - Raquel de Oliveira (2023)
Homonymous lexical units (HLU) have identical forms (whether oral or written), expressing, however, different contents. As a result of this linguistic characteristic, homonymy can cause lexical ambiguity, resulting in a great challenge, especially for foreign language learners. Indeed, there are three basic types of homonymy, namely: homograph homophones (which have the same pronunciation and spelling, but different meaning); non-homograph homophones (which have the same pronunciation, but different spelling and meaning); and non-homophone homographs (which have the same spelling, but different pronunciation and meaning). In the Lexicography scenario, lexical units that have different semantic values, the same pronunciation and different spelling, we have HLU that do not always receive consistent treatments according to its functional and pragmatic characteristics in lexicographical repertoires, as we have demonstrated with the development of this research. Because of that, in this context, we emphasize the need for a special lexicographical treatment of HLU, especially in the context of Pedagogical Lexicography (LEXPED). Thus, the general objective of this Master's research, which we are developing within the scope of the Post-Graduate Program in Linguistics at UFMS/CPTL, is to identify and analyze how non-homographs homophones are registered in learner’s dictionaries of English as a foreign language and, then, to elaborate a proposal for a homogeneous lexicographical treatment of these homonymous forms in these dictionaries, so that their didactic character is enhanced. In order to do so, we are guided by the theoretical and methodological principles of LEXPED in its interface with the area of foreign language teaching and learning, as well as with the area of phonology of the English language, these being some of the authors we consulted: Ullmann (1973), Biderman (1978), Berruto (1979), Underhill (1994), Garriga Escribano (2003), Zavaglia (2003), Scrivener (2005), among others. In this perspective, we selected 14 (fourteen) homophone lexical units, which we looked up in 20 (twenty) dictionaries selected for analysis, among which are bilingual printed dictionaries, monolingual printed dictionaries and internet dictionaries (some monolingual and some bilingual). In this research, we looked up these lexical units in the dictionaries, observing if they presented any explicit record of homophony cases or if they relegated to the user the task of comparing the pairs/trios of non-homograph homophones and concluding on their own that there is sound similarity between them. Up to the present moment, among the works we have analyzed, we found that only three of the Oxford publisher's dictionaries provide explicit information on Non-Homograph Homophones to the users. Thus, after identifying some gaps in the analyzed works, we developed a prototype of a monolingual online dictionary for non- Homograph Homophones, which is already in operation. We emphasize that many of the proposals we made are innovative, as they break with existing lexicographical traditions and were not found in any of the analyzed repertoires. Finally, considering all the reflections conducted around our object of study, we hope that these may be useful for the elaboration of new dictionaries in the years to come.